SIFAT FISIKA DAN KIMIA TANAH INCEPTISOL DENGAN PERLAKUAN KOMPOS (Physical and Chemical Characteristics of Inceptisolsoil Treated with Compost) - Indah Purnama Harahap; Sumono Sumono; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT   Physical and chemicalcharacteristic of inceptisolare important  factors for the growth of plant. The objective of this research was to know the effect of compost application onphysical and chemical characteristics of inceptisol soil. The design used was completely randomized design consist of 4 (four) treatments and 3 replicationsie:K1= without compost, K2= 9 Kg inceptisol soil+1 kg compost, K3= 8 kg inceptisol soil +2 kg compost, K4= 7 kg inceptisol soil+3 kg compost. The observed parameters were soil texture, soil organic matter, porosity, water content of field capasity, soil permeability, pH, total Nitrogen, Phosphoravailable soil, Kexchangeof soil.The results showed that the soil type was inceptisolwithsandy loamtexture;soil organic matter was from 1,31 to 5,86%, porosity was from 51,94 to 56,40 % , Permeability was from 4,52 to7,39 cm/jam, The water content of field capacityatPF 2,54 was from 37,93 to 50,74% and atPF 4,2 was  from 30,39 to 41,68% therefore, water available was  from 7,54 to 9,06%, pH was increased from 7,21 ( netral)  to 7,46 (netral), N of soil wasfrom0,1100 to 0,2200%, Pof soil wasfrom 11,4567 to38,2000ppm. Kexchangeof soil was from0,5050 to 0,6867me/100g. Keyword: Soil Physical And Chemical Characteristic,Inceptisol, Compost. ABSTRAK Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan tanaman.Penelitian iniuntuk mengetahui pengaruh pemberian bahan organik  terhadap sifat fisik dan kimia tanah inceptisol.Penelitian menggunakan rancangan acak lengkap non faktorial, terdiri dari 4 perlakuan dan 3 ulangan, yaitu K1 (tanpa kompos), K2=  9 kg tanah inceptisol+1 kg kompos, K3= 8 kg tanah inceptisol+2 kg kompos, K4= 7 kg tanah inceptisol+3 kg kompos. Parameter yang diamati meliputi tekstur tanah, bahan organik,  porositas, kadar air kapasitas lapang, permeabilitas tanah, pH, N-total, P tersedia dan K tukar tanah.Hasil penelitian menunjukkan jenis tanahinceptisol adalah bertekstur lempungberpasir, bahan organik tanah berkisar 1,31-5,86%, porositas berkisar51,94-56,40 %, permeabilitas berkisar4,52-7,39 cm/jam, kadar air kapasitas lapang pada PF 2, 54 berkisar37,93- 50,74%, PF 4,2berkisar30,39-41,68% sehingga air tersedia 7,54-9,06%, pH meningkat 7,21 (netral)-7,46 (netral). Kandungan N dalam tanah berkisar 0,1100-0,2200%, P dalam tanah berkisar11,4567-38,2000 ppm, K tukar tanah berkisar 0,5050-0,6867me/100g. Kata Kunci: Sifat Fisika Dan Kimia Tanah, Inceptisol, Kompos